CO2 Sequestration Through Aqueous Carbonation of Electric Arc Furnace Slag - Bonfante, Francesca; Ferrara, Giuseppe; Humbert, Pedro; Garufi, Davide; Tulliani, Jean-Marc Christian; Palmero, Paola (Journal of Advanced Concrete Technology, 2024)
Electric Arc Furnace slag (EAF slag) reuse is currently limited by its inconsistent chemical composition and volume instability. However, the alkaline composition suggests the possibility to use this material for carbon capture and storage. This study investigated the CO2 uptake of EAF slag using a direct aqueous carbonation technique. The process was implemented at room temperature and ambient pressure, with minimized energy consumption. The CO2-reactive phases were identified through X-ray diffraction analysis. Different CO2 quantification techniques were employed: thermogravimetric analysis, acid digestion and thermal decomposition. The replicability of experiments and quantification techniques was assessed through analysis of variance and pairwise comparisons. The average CO2 uptake and coefficient of variation resulted respectively 7.9% and 9.0%, with a carbonation degree of about 34%, proving that this simple mineralization process can be promising even in mild conditions.